Effects of Exogenous Plant Hormones on Agronomic Traits and Physiological Responses of Elymus sibiricus - Qi Yuan; Juan Qi; Wenhui Liu; Wangyi Du; Mingjie Li (Agriculture)
As key endogenous signal molecules regulating plant growth processes, plant hormones have significant applications in forage breeding. The experiment used ‘Elymus sibiricus Qingmu No. 2’ as the test material, and the effects of foliar applied phytohormones of gibberellin (GA3: 50, 100, 200, and 300 mg/L), cytokinin (6-BA: 1, 10, 100, and 150 mg/L), epibrassinolide (EBR: 0.01, 0.1, 1, and 10 mg/L), zeatin (ZT: 1, 10, 20, and 100 mg/L), and auxin (IAA: 10, 50, 100, and 150 mg/L) on growth and physiological responses in Elymus sibiricus were investigated. The results indicated that GA3 at 200 mg/L significantly enhanced biomass by 38.19%, plant height by 75.11%, and leaf area by 40.58% compared to controls. IAA (150 mg/L) specifically increased stem diameter by 38.25%, while 6-BA (100 mg/L) elevated chlorophyll content and antioxidant enzyme activities, indicating dual photoprotective and stress-mitigating roles. EBR (1 mg/L) and ZT (20 mg/L) moderately enhanced growth metrics. All treatments universally boosted stress tolerance via soluble sugar/protein accumulation and antioxidant system activation. Through comprehensive analysis, we recommend GA3 (200 mg/L) for effective grassland improvement, propose synergistic combinations of 6-BA and IAA to overcome morphological limitations, and highlight ultra-low EBR (0.01–0.1 mg/L) as a priority for future research.